Gold nanoplates for a localized surface plasmon resonance-based boric acid sensor - Morsin, Marlia; Mat Salleh, Muhamad; Umar, Akrajas Ali; Sahdan, Mohd Zainizan (MDPI, 2017)
Localized surface plasmon resonance (LSPR) properties of metallic nanostructures, such as gold, are very sensitive to the dielectric environment of the material, which can simply be adjusted by changing its shape and size through modification of the synthesizing process. Thus, these unique properties are very promising, particularly for the detection of various types of chemicals, for example boric acid which is a non-permitted preservative employed in food preparations. For the sensing material, gold (Au) nanoplates with a variety of shapes, i.e., triangular, hexagonal, truncated pentagon and flat rod, were prepared using a seed-mediated growth method. The yield of Au nanoplates was estimated to be ca. 63% over all areas of the sensing material. The nanoplates produced two absorption bands, i.e., the transverse surface plasmon resonance (t-SPR) and the longitudinal surface plasmon resonance (l-SPR) at 545 nm and 710 nm, respectively. In the sensing study, these two bands were used to examine the response of gold nanoplates to the presence of boric acid in an aqueous environment. In a typical process, when the sample is immersed into an aqueous solution containing boric acid, these two bands may change their intensity and peak centers as a result of the interaction between the boric acid and the gold nanoplates. The changes in the intensities and peak positions of t-SPR and l-SPR linearly correlated with the change in the boric acid concentration in the solution.